Additives incorporated into urea to reduce nitrogen losses after application to the soil - Rech, Ioná; Polidoro, José Carlos; Pavinato, Paulo Sergio (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to develop urea-based fertilizers with internal incorporation of urease inhibitors and other additives in the granule. The effects of the incorporation of NBPT, copper (Cu+2), boric acid (H3BO3), elemental sulphur (Sº), and a clay mineral from the zeolite group in powder urea – with ten different combinations of these additives – were evaluated as to N losses by volatilization and leaching. The losses in laboratory-developed formulations were compared with those of commercial fertilizers coated with the same additives (Super N, FH Nitro Mais, and FH Nitro Gold). The evaluations were made in greenhouse conditions, using a Ultisol accommodated in PVC columns. Nitrate and ammonium leaching was evaluated in the solution percolated through the soil columns. Ammonia volatilization was measured with a semi-open static chamber. The incorporation of urease inhibitors (NBPT, H3BO3, and Cu+2) into the urea granules was efficient to reduce N volatilization. Ammonia volatilization in the laboratory-developed ureas was lower than in commercial fertilizers coated with the same additives, while ammonium sulfate losses by leaching were similar. The addition of zeolite does not reduce N volatilization. Mineral N leaching in the soil profile is not affected by urease inhibitors.
Keywords: ammonia volatilization; leaching; NBPT; nitrogen fertilizers; urease inhibitors